2017
DOI: 10.3390/molecules22101508
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Moniliella spathulata R25L270 Lipase on Ionic, Hydrophobic and Covalent Supports: Functional Properties and Hydrolysis of Sardine Oil

Abstract: The oleaginous yeast Moniliella spathulata R25L270 was the first yeast able to grow and produce extracellular lipase using Macaúba (Acrocomia aculeate) cake as substrate. The novel lipase was recently identified, and presented promising features for biotechnological applications. The M. spathulata R25L270 lipase efficiently hydrolyzed vegetable and animal oils, and showed selectivity for generating cis-5,8,11,15,17-eicosapentaenoic acid from sardine oil. The enzyme can act in a wide range of temperatures (25–4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…The temperature is an important parameter for the properties of enzymes [49,50,51,52]. The DFF yield was studied as a function of temperature ranging from 15–45 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature is an important parameter for the properties of enzymes [49,50,51,52]. The DFF yield was studied as a function of temperature ranging from 15–45 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The construction of an in vitro biofriendly microenvironment plays an important role in maintaining the high catalytic activity of the enzyme, and surfactants are often used to form enzyme surfactant micelles that show significantly higher efficiency [ 29 , 30 ]. It has been confirmed that the higher activity is a result of the structure of the surfactant and the interaction between the micelle-bound enzyme and the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…The main type of interaction between the enzyme and lecithin is electrostatic, because of the large number of positive and negative charges on the surface of the enzyme and lecithin, which can alter the conformation and activity of the enzyme to some extent. In particular, at low concentrations, lecithin, contains a monovalent quaternary ammonium cation, binds to the lipase through weak electrostatic interactions, which alter the conformation of the enzyme and allow it to combine with the substrate more easily [ 30 ]. Nevertheless, as the concentration of lecithin increased, a decay phenomenon emerged in the relative activity of the lipase.…”
Section: Resultsmentioning
confidence: 99%
“…Lipases are used in free form as an active ingredient in foods, such as bakery and pasta products, and various types of cheese and dairy products to improve the quality and taste of the final product [24,[26][27][28] or in immobilized form to provide a substitute for human milk [27,28], cocoa butter [29][30][31][32], specific flavors as food additives [33], or for the production of ω-3-and ω-6-fatty acids from fish and other oil species [34,35]. Although lipase accounts for about 10% of all industrial enzymes used in current industrial production, the use of these enzymes is expected to increase due to their versatility [24,[36][37][38][39].…”
Section: Lipases As Heterogeneous Biocatalystsmentioning
confidence: 99%